Ice Cakes at Forty Mile, T. Ter. 15 Feet Thick. May 23, 1901 - Howard, Mart Albert, 1855-1926 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1901)
1 Lantern Slide: b&w; 10 x 8 cm. Ice cakes in front of a Alaska Commercial Company building in Forty Mile, Yukon Territory. Photo by Goetzman, Dawson. 1958.